Differential cytotoxicity of ethyl acetate extracts of Malaysian marine endophytic fungi (MBS3.2 and SM1.4 PLATE 1) against human breast cancer cell lines - Hendarto, Nursyafira (2016)
Endophytes-derived metabolites, which are known to exhibit anticancer and antimicrobial activities, are progressively becoming significant in discovery of novel drugs. Given the abundance of unexplored Malaysian endophytes within marine plants, this study was carried out to assess the cytotoxic profiles of ethyl acetate endophytic fungal extracts MBS3.2 (originated from Sonnaratia sp.) and SMI.4 PLATE }(originated from sea mud) against human breast cancer cells. The fungal cultures were first examined using gross observation and ESEM. The cultures were then extracted using rotary evaporator. The resultant extracts (0.01 - 100 µg/mL) were tested against MCF7 (ER positive breast cancer cells) and MDA468 (ER negative breast cancer cells) for 72 h. SRB assay was performed and data generated was used to plot dose-response curve from which the ICso ( concentration that inhibit 50% cells population) was obtained. The present found MBS3.2 and SMI.4 PLATE 1 to be more selective towards MCF7. They were, however, modest cytotoxic agents against human breast cancer cells, yielding ICso > 20µg!mL. This warrants future studies against other cancer types.